Meningkatkan kesejahteraan masyarakat di Desa Notorejo melalui distribusi Zakat Kreatif - aini, Intan Nur’ (Maliki Interdisciplinary Journal, 2023)
Zakat is giving a portion of the property owned and having attained nishab for one year. Zakat should be issued to every Muslim both from children and adults. Zakat is distributed through amils or agencies that have been assigned tasks by the central government. In Indonesia, the government has established BAZNAS as an institution that distributes zakat. The purpose of zakat has been regulated in Law No. 23 of 2011. However, many people have not felt or achieved this goal. Such is the case in Notorejo Village where the poor have not felt welfare with zakat. The use of zakat itself has been regulated in Law No. 23 of 2011 article 27. In accordance with this law, Notorejo Village created an industrial business to make roof tiles for the poor using a creative productive distribution system. The goal is that people can feel the benefits of receiving zakat in the long run. The business system uses the concepts of mudharabah and qardhu hasan. This research uses qualitative methods.